Avaliação do efeito da vitamina D na doença de Parkinson: foco na função mitocondrial e estresse oxidativo - Lima, Ludmila Araújo Rodrigues (2023)
Parkinson's disease (PD) characterized by loss of neurons in the substantia nigra, dopamine depletion, and accumulation of Lewy bodies. It has a complex etiopathogenesis involving multiple pathways, including mitochondrial dysfunction, oxidative stress and neuroinflammation. Scientific evidence supports the neuroprotective effects of vitamin D (VITD) in PD. The present study aims to evaluate the effects of VITD supplementation on alterations in mitochondrial function and oxidative stress, in a model of PD induced by unilateral stereotaxic injection of 6- OHDA. Male Wistar rats (250-300g) were divided into the following groups: FO (sham), 6-OHDA (12μg/μl), PRE-TTO (1μg/kg/day, oral, 7days + 6-OHDA) and POST- TTO (6- OHDA + 1μg/kg/day, orally, 14 days). Following the protocol, the animals were submitted to behavioral tests, euthanized and neurochemical and immunohistochemical evaluations were performed. Data were analyzed by ANOVA (Tukey or Bonferroni or Kruskal-Wallis and Dunn) and p<0.05 was considered significant. Both VITD supplementation protocols were effective in restoring motor behavior, via apomorphine-induced rotational behavior and the open field test, and depressive-like behavior, via the forced swim test. In addition, the PRE-TTO group showed, for all analytes, restoration of bioenergetic activity, mitochondrial swelling and membrane potential, as well as mitigating oxidative effects, through an increase in the concentration of cytosolic superoxide dismutase (SOD) and a decrease in levels of mitochondrial hydrogen peroxide (H2O2). In addition, VITD supplementation protected the hemiparkinsonian brain from decreases in Tyrosine hydroxylase (TH) and Dopamine Transporter (DAT) expression and decreased the upregulation of mitochondrial markers such as Voltage-dependent Anion Channel 1 (VDAC 1) and Protein of thermal shock 60 (Hsp60). In conclusion, VITD showed neuroprotective actions in brain mitochondria damaged by 6-OHDA and should encourage translational studies focusing on its use as a therapeutic strategy for the treatment of neurodegenerative diseases such as PD.